2017
DOI: 10.1371/journal.pone.0186809
|View full text |Cite
|
Sign up to set email alerts
|

Temperate grassland songbird species accumulate incrementally along a gradient of primary productivity

Abstract: Global analyses of bird communities along elevation gradients suggest that bird diversity on arid mountains is primarily limited by water availability, not temperature or altitude. However, the mechanism by which water availability, and subsequently primary productivity, increases bird diversity is still unclear. Here we evaluate two possible mechanisms from species-energy theory. The more individuals hypothesis proposes that a higher availability of resources increases the total number of individuals that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…the Great Kiskadee (Pitangus sulphuratus) or the Rufous Hornero (Furnarius rufus). On the other hand, the NP hypothesis is consistent with a gradual change of species composition along the disturbance gradient (Harrower et al 2017). Indeed, our data showed that bird communities along the urban-rural gradient were dominated by different species (Table 2).…”
Section: Conservation Implicationssupporting
confidence: 86%
See 2 more Smart Citations
“…the Great Kiskadee (Pitangus sulphuratus) or the Rufous Hornero (Furnarius rufus). On the other hand, the NP hypothesis is consistent with a gradual change of species composition along the disturbance gradient (Harrower et al 2017). Indeed, our data showed that bird communities along the urban-rural gradient were dominated by different species (Table 2).…”
Section: Conservation Implicationssupporting
confidence: 86%
“…The three processes tested have different management decisions to increase species richness along urbanization gradients (Harrower et al 2017). If the HH hypothesis was supported, only efforts to create more diverse habitats would be adequate.…”
Section: Conservation Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These regions tend to be drier with more sparse vegetation, as well as lower soil moisture and productivity. While these regions provide critical habitat for aridland bird species such as Brewer's Sparrow, they are less suitable for grassland birds that prefer lusher and more productive habitats (Fedy et al., 2018; Fisher & Davis, 2010; Harrower et al, 2017; Renfrew et al., 2013). As a result, they have fewer bird species, many of which share similar functional traits (e.g., ground‐dwelling insect‐ and granivores; Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Higher productivity supports a greater number of individuals, thereby reducing local species extinction rates and supporting a greater number of species (Srivastava & Lawton, 1998). Harrower et al (2017) suggest that for grassland songbirds, higher productivity may translate to greater availability of resources such as plant biomass and prey abundance, thus indirectly supporting avian abundance and species richness. Across North America, the most productive areas have undergone extensive land‐use change and are overwhelmingly under heavy human use (Scott et al, 2001).…”
Section: Introductionmentioning
confidence: 99%